Organizational stressors, social support, and implications for subjective performance in high-level sport - Arnold, R.; Edwards, T.; Rees, T. (Psychology of Sport and Exercise, 2018)
Objectives: Although much is now known about the role of social support in the competitive stress process, scholars have yet to examine this moderator in relation to organizational stress. The purpose of this study was to examine the relationship between perceived organizational stressors and subjective performance in sport, with particular focus on the potential moderating role of social support. Design and methods: Talented athletes (N = 122; 60 male; Mage = 20.50) completed questionnaires of perceived organizational stressors, social support, and subjective athletic performance. Results: In addition to evidence of main effects, analyses revealed four significant interactions which demonstrated that social support did act as a significant moderator of the relationship between organizational stressors and subjective performance. Contrary to the extant literature, however, the findings illustrated reverse buffering. Associations suggest that some dimensions of social support exacerbated rather than mitigated athletes' stress reactions (i.e. impaired performance) when encountering greater frequencies of organizational stressors. Conclusion: These findings not only advance theoretical understanding of the organizational stress process, but also present a number of significant implications for athletes, coaches, and applied practitioners aiming to enhance performance in pressurized and demanding situations. Specifically, recommendations are forwarded for practitioners to address coaching stressors and provide effective social support that is matched to the stressors that he or she encounters.